Common law in the scientific legacy of Ivan Luchitskiy - Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the general theoretical looks of Ivan Luchitskiy according to the role of norms of common lawin adjusting of public relations in Ukrainian earths in XVI-XVIII centuries are dealt with. The researches of scientist in relation to a character and forms of communal landownership, legal status of the Ukrainian peasantry, customarinessin contract and marriage-domestic law are analyzed.